A Performance and Usability Aware Secure Two-Factor User Authentication Scheme for Wireless Sensor Networks - Sang Guun Yoo; Hyukjun Lee; Juho Kim (International Journal of Distributed Sensor Networks)
Recently, several user authentication schemes for wireless sensor networks based on two-factor concept using the smart card technology were proposed. However, they have serious limitations in terms of security and usability. First, even though they are enhancements of other works, they still have several security flaws, such as vulnerability against parallel session, privileged-insider, and gateway-node bypassing attacks and lack of mutual authentication between user station and gateway node. On the other hand, they also present a usability constraint, in a sense that they do not consider the use case when sensor nodes cannot communicate with gateway node. In this case, data collected by isolated sensor nodes could not be accessed until they recover such communication, which is in many times not recoverable rapidly or forever (e.g., military applications, natural disaster monitoring). Due to all these reasons, this paper proposes a robust user authentication scheme which fixes the security weaknesses of previous solutions and provides wider usability considering the use case when the sensor nodes cannot communicate with the gateway node. Once the solution is described, its security is ensured by formal proof and analysis against attacks. Additionally, performance and cost analysis are executed to determine its level of feasibility for real implementation.